Low Carbon Mobility: Appraisal of Case of Rajkot - Sharma, Vijay Kumar; ., Chetna (Journal of Advanced Research in Alternative Energy, Environment and Ecology, 2021)
Our cities are growing rapidly and so as the transport network. The land use planning and transport are interdependent and interlinked. But, eventually with this growth there is negative impact on the environment. Transportation contributes to 27% of carbon footprint and this is still growing with the growth of cities and its network system and the nature of societies. When even we talk about the planned strata the behavior of vehicles and tendency of user is the alarmed observation which can be noticed by increase in number of private vehicles. This contributes even to GHG Emissions which negatively impact the environment and human health and leads to the birth of chronic diseases. How to cite this article: Chetna, Sharma VK. Low Carbon Mobility: Appraisal of Case of Rajkot. J Adv Res Alt Energ Env Eco 2018; 5(4): 6-9.